2022
DOI: 10.1002/ange.202212889
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Spirosilabicyclohexenes by Asymmetric Dual Ring Expansion of Spirosilabicyclobutane with Alkynes

Abstract: Silaspiranes have attracted particular attention due to their chiral spiro‐silicon center, which serves as an ideal carbon isostere and can endow spiro‐analogs with distinct properties. Distinct from previously reported cyclization or cycloaddition strategies to form 5/5‐silaspiranes, we report herein the asymmetric dual ring expansion of spirosilabicyclobutanes with alkynes to synthesize axially chiral spirosilabicyclohexenes bearing a novel 6/6‐silaspirane framework. DFT (density functional theory) calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…Recently, we developed a rhodium-catalyzed asymmetric dual ring expansion of spirosilabicyclobutanes with alkynes to synthesize C 1 -or C 2 -symmetric 6/6-spirosilabicyclohexenes. 10 The sterically demanding binaphthyl phosphoramidite ligands played a key role in constructing the stereogenic silicon with high enantioselectivity. We envisioned that such sterically demanding ligands might also find good applicability in the ring expansion of other silacyclobutane-containing silaspiranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we developed a rhodium-catalyzed asymmetric dual ring expansion of spirosilabicyclobutanes with alkynes to synthesize C 1 -or C 2 -symmetric 6/6-spirosilabicyclohexenes. 10 The sterically demanding binaphthyl phosphoramidite ligands played a key role in constructing the stereogenic silicon with high enantioselectivity. We envisioned that such sterically demanding ligands might also find good applicability in the ring expansion of other silacyclobutane-containing silaspiranes.…”
mentioning
confidence: 99%
“…In our previous work on the asymmetric construction of 6/ 6-spirosilabicyclohexenes via dual ring expansion of 4/4spirosilabicyclobutanes, DFT calculations suggested that oxidative addition was reversible and migration insertion was the enantioselectivity-determining step. 10 We hypothesized that such a model could also apply to the ring expansion of 1monosubstituted 4/5-spirosilafluorenes developed in this work (Scheme 6). The transition-state models of TS-R and TS-S were proposed using 1a and phenylacetylene.…”
mentioning
confidence: 99%